2014
DOI: 10.1111/joa.12182
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory genotype–phenotype correlations of facial form and asymmetry in unaffected relatives of children with non‐syndromic cleft lip and/or palate

Abstract: Family relatives of children with nonsyndromic cleft lip with or without cleft palate (NSCL/P) who presumably carry a genetic risk yet do not manifest overt oral clefts, often present with distinct facial morphology of unknown genetic etiology. This study investigates distinct facial morphology among unaffected relatives and examines whether candidate genes previously associated with overt NSCL/P and left–right body patterning are correlated with such facial morphology. Cases were unaffected relatives of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 95 publications
(150 reference statements)
2
38
0
3
Order By: Relevance
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies of shape in Drosophila found no significant directional asymmetry of wing shape [115][116][117][118][119] or mixed results [120][121][122][123][124][125][126], although a series of other studies did find it [15,16,54,56,62,77,85,123]. Similarly, one study on human skulls [127] found no directional asymmetry of shape, whereas several others reported directional asymmetry of the skull [47,68,84,86,90,94,109] and soft tissues of the face and ears [38,66,98,104,105,108]. Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens.…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…Several studies have mapped quantitative trait loci with effects on fluctuating asymmetry in mouse mandibles [45,107,392], mouse skulls [64], Drosophila wings [77], and human faces [98]. These studies found at least some loci with effects on fluctuating asymmetry, but it is likely that such analyses have limited statistical power with the experimental sizes that are feasible in most cases.…”
Section: Inheritance Of Fluctuating Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Only in families with a history of cleft-lip/palate was asymmetry (pattern discordance) greater than that of the controls. Recently, Miller et al [70] identified three genes associated with facial asymmetry (actually directional asymmetry) in the relatives of nonsyndromic cleft lip with or without cleft palate; these genes are LEFTY1, LEFTY2, and SNAI1.…”
Section: Medicinementioning
confidence: 99%
“…Linear measurements, such as deviations of eye, ear, nostril, and cheek horizontal midpoints from the facial mid-line [69] are common, as are two-and three-dimensional imaging [30,70] and landmark methods for shape asymmetry (geometric morphometrics) [28,41]. In addition to linear measurements, landmark methods of geometric morphometrics have recently been used to study shape asymmetry of the dental arch [68].…”
Section: Facial Asymmetrymentioning
confidence: 99%